Cosmochemistry: Exploring the Origins and Distribution of Elemental Abundances in the Universe - Goshu, Belay Sitotaw (Budapest International Research in Exact Sciences (BirEx) Journal, 2025)
This study explores the spectrum analysis of celestial objects within the wavelength range of 1000 nm to 2400 nm, focusing on its application in understanding the chemical and thermal evolution of the universe. The emergence of light elements like hydrogen and helium was made possible by primordial nucleosynthesis, which took place not long after the Big Bang and provided vital evidence in favor of the Big Bang theory. The production of heavier elements in stars is known as stellar nucleosynthesis, and this process is thoroughly studied. The significant factor in the various nucleosynthetic processes placed within stars is temperature. The study also delves into the galactic chemical evolution, tracing the enrichment of elements like carbon, oxygen, and iron over time through repeated cycles of star formation and stellar death. The research highlights how temperature evolution in galactic chemical processes influences star formation and cooling mechanisms, impacting the overall chemical composition of galaxies. The spectrum analysis in the near-infrared range allows for the findings of these processes even in dust-enshrouded regions, offering deeper insights into stellar and galactic evolution. These findings contribute to a more comprehensive understanding of how the universe's chemical and thermal makeup has changed since its inception.